2017
DOI: 10.1016/j.apsusc.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metal layer stacking order on the growth of Cu2ZnSnS4thin films

Abstract: In this paper we have presented an in-depth study of effect of metallic precursor stacking order on the growth of the Cu 2 ZnSnS 4 (CZTS) thin films. The CZTS films were prepared by employing a two-step process comprising of sequential sputtering of the metal precursors followed by sulfurization. An optimized stacking sequence as well as growth mechanism for obtaining the single phase CZTS has been proposed based on the results of XRD, Raman, XPS, UV-Vis and electrical studies. A combination of Raman analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…It demonstrates that all absorbers share a very similar pattern which agrees well with that of tetragonal kesterite CZTS (JCPDS No. 026-0575) with the preferred orientation of CZTS at (112) consistent with the literature [15,16]; the full width at half maximum (FWHM) of the main peak (112) of CZTS has a small dip down from 0.165 • to 0.158 • , then increases by 0.17 • and ends at 0.228 • with increasing the precursor deposition pressure from 5 to 12.5 mTorr. This FWHM trend is consistent with the SEM results as small FWHM reflects large grain size and a low defect level inside the film.…”
Section: Resultssupporting
confidence: 66%
“…It demonstrates that all absorbers share a very similar pattern which agrees well with that of tetragonal kesterite CZTS (JCPDS No. 026-0575) with the preferred orientation of CZTS at (112) consistent with the literature [15,16]; the full width at half maximum (FWHM) of the main peak (112) of CZTS has a small dip down from 0.165 • to 0.158 • , then increases by 0.17 • and ends at 0.228 • with increasing the precursor deposition pressure from 5 to 12.5 mTorr. This FWHM trend is consistent with the SEM results as small FWHM reflects large grain size and a low defect level inside the film.…”
Section: Resultssupporting
confidence: 66%
“…Su et al [15] fabricated CZTS films through sequential electrodeposition of metallic precursors and observed that the compositional ratio and stacking order have a major role in CZTS phase formation and they successfully prepared a 93% phase pure CZTS film with a glass/Zn/Sn/Cu precursor stack. Recent studies from Thota et al [20] and Olgar et al [21] also reveal that films having a Cu layer adjacent to both Sn and Zn layers have enhanced performance as an absorber layer due to the uniform diffusion of the precursor layers while annealing. Also, Thota et al [20] studied the effect of all the three constituent metallic layers as the capping layer and found that films with Cu at the top of stacking have enhanced electrical characteristics due to the minimal loss of volatile Sn and Zn from the precursor.…”
Section: Introductionmentioning
confidence: 98%
“…Recent studies from Thota et al [20] and Olgar et al [21] also reveal that films having a Cu layer adjacent to both Sn and Zn layers have enhanced performance as an absorber layer due to the uniform diffusion of the precursor layers while annealing. Also, Thota et al [20] studied the effect of all the three constituent metallic layers as the capping layer and found that films with Cu at the top of stacking have enhanced electrical characteristics due to the minimal loss of volatile Sn and Zn from the precursor. Kim and Yoo [13] also concluded that films prepared with Cu at the top have enhanced grain sizes which may lead to superior performance.…”
Section: Introductionmentioning
confidence: 98%
“…[11,12] On the other hand, almost no limitations were observed for vacuum-based processes allowing to exploit different stacking order combinations. [13][14][15][16][17][18][19][20][21][22] In this context, literature studies demonstrated the advantages that are achieved through alternative sequences. In fact, the evaporation of Zn and Sn during reactive annealing may result in the formation of voids and a significant variation in the film stoichiometry.…”
Section: Introductionmentioning
confidence: 99%
“…[23,24] The loss of the former is particularly critical since a zinc-rich copper-poor stoichiometry is associated with high-performing energy conversion devices. [24,25] Therefore, capping the zinc layer with Sn or Cu resulted in a lower evaporation rate and a more compact morphology, [13,[18][19][20] leading to a higher photoconversion efficiency. [13] Moreover, when Sn and Cu layers are adjacent, the formation of CuÀ Sn intermetallic and corresponding sulfides reduces the tin loss.…”
Section: Introductionmentioning
confidence: 99%